Why Left-handers/footers are overrepresented in some sports? - Selcuk Akpinar; Bilal Bicer (Montenegrin Sports Academy, 2014)
Left-handers/footers are found with disproportionately more frequency in many interactive sports compared to the general po¬pu¬lation. In ıorder to point out this issue, we firstly mentioned about handedness in general and secondly the origin of handedness. Ba¬sed on the studies in the literature, we then gave examples about the anatomical correlation of handedness. Finally, some expla¬na¬tions were provided to explain the higher rate of lefties in some sports compared to the general population. Regarding the last issue, researchers stated that there are mainly two possible hypotheses to explain this phenomenon; innate superiority and negative fre¬quency hypothesis. Besides those hypotheses, we should also consider that there is a need to have left handed/footed players in so¬me sports to get more tactical advantages. We tried to give some examples regarding those ideas. The studies in the literature sta¬te that left handed/footed players, in fact, have both tactical and perceptual advantages in some interactive sports and thus, over¬represented in those sports compared to the general population.